EFEK ANTIHIPERTENSI FRAKSI TIDAK LARUT KLOROFORM EKSTRAK ETANOLIK DAUN PEGAGAN (Centella asiatica (L.) Urban) PADA TIKUS TERINDUKSI FENILEFRIN - , Esy Nansy ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Hypertension is a risk factor for cardiovascular diseases. In Indonesia , 22,8 % of the population suffer from hypertension. People use tradisional remedies or medicinal plants for curing hypertension, such as Centella asiatica (L) Urban). Triterpenoids and flavonoids contents of the leaves are potensial to be developed as antihypertensive compounds and these two chemical constituent groups have different polarities so they can be separated by fractionation using different solvents. The triterpenoid fraction has been reported having antihypertension effect therefore this research were emphasized on the antihypertension effect of flavonoid fraction of leaves ethanolic extract. The dried leaves powder was macerated with 70% ethanol and fractionated with chloroform. Thin layer chromatogram data on silica F254 with mobile phase of butanol